Systematic Investigation of Structural, Morphological, Thermal, Optoelectronic, and Magnetic Properties of High-Purity Hematite/Magnetite Nanoparticles for Optoelectronics - Akbar Ali Qureshi; Sofia Javed; Hafiz Muhammad Asif Javed; Muhammad Jamshaid; Usman Ali; Muhammad Aftab Akram (Nanomaterials, 2022)
Iron oxide nanoparticles, especially hematite (α-Fe2O3) and magnetite (Fe3O4) have attained substantial research interest in various applications of green and sustainable energy harnessing owing to their exceptional opto-magneto-electrical characteristics and non-toxicity. In this study, we synthesized high-purity hematite and magnetite nanoparticles from a facile top-down approach by employing a high-energy ball mill followed by ultrasonication. A systematic investigation was then carried out to explore the structural, morphological, thermal, optoelectrical, and magnetic properties of the synthesized samples. The experimental results from scanning electron microscopy and X-ray diffraction corroborated the formation of highly crystalline hematite and magnetite nanoparticles with average sizes of ~80 nm and ~50 nm, respectively. Thermogravimetric analysis revealed remarkable results on the thermal stability of the newly synthesized samples. The optical studies confirmed the formation of a single-phase compound with the bandgaps dependent on the size of the nanoparticles. The electrochemical studies that utilized cyclic voltammetry and electrochemical impedance spectroscopy techniques verified these iron oxide nanoparticles as electroactive species which can enhance the charge transfer process with high mobility. The hysteresis curves of the samples revealed the paramagnetic behavior of the samples with high values of coercivity. Thus, these optimized materials can be recommended for use in future optoelectronic devices and can prove to be potential candidates in the advanced research of new optoelectronic materials for improved energy devices.